Prevalence of Cryptosporidium Infection in Calves with Effect on Biochemical Parameters - Osamah Nasir Wali1 , Ayoub Ibrahim Ali2 , Khalid Ismael Oleiwi3, Mustafa Salah Hasan3 , Mohammed Ham (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was conducted throughout the year on 93 calves from different regions of Baghdad province.Three age groups included; Below 1 month, 1-2 months and above 6 months. A changed aim-the techniqueof stain Neelsen (MZN) has been used for the identification of the development of cryptosporidium and fecaldiarrheic samples.In biochemical research, blood samples have been obtained. Cryptosporidium occurrence was much higherin spring season (56%), followed by the winter (52%), the allergy season (46%), and lowermost in a seasonof summer (40%).The highest rate of infection in animals which was given was the age group of theanimals that under the age of 30 days (71%), 2-6 months were (59%) and (43%) were over 6 months old.The animals concerned reported substantial rises in plasma, urea and creatinine relative to stable animalsin the management of biochemical changes. Finally, Age and seasonal changes were associated withcryptosporidiosis. The biochemical factors affected by the calves also have a negative effect.